Cystic fibrosis: when neonatal screening is unsatisfactory for early diagnosis - Carolina Godoy; Igor Radel; Laís Ribeiro Mota; Marília Augusta Santos; Regina Terse; Edna Lúcia Souza (Instituto Materno Infantil de Pernambuco, 2024)
Abstract Introduction: cystic fibrosis newborn screening must enable its earlier diagnosis, which may enhance outcomes. This study was a series case of delayed-diagnosis children submitted to cystic fibrosis newborn screening. Description: fourteen children were included; eight (57.1%) were due to false-negative screening, while six (42.9%) were due to processing errors. Two samples collected after 30 days of life were incorrectly classified as negative, and four infants with a positive test could not be located due to screening processing errors. Cystic fibrosis diagnosis was confirmed at a median (IQR) age of 5.3 (4.2-7.4) months. Poor nutritional status was the most prevalent clinical sign at diagnosis, being present in 78.6% of infants. The mean (SD) weight-for-length and length-for-age Z-scores were -3.46 (0.84) and -3.99 (1.16), respectively. Half of the children had Pseudo-Bartter syndrome, and 42.9% had breathing difficulties. Twelve children (85.7%) required hospitalization, with a median (IQR) length of stay of 17.0 (11.5-26.5) days. Discussion: newborn screening had some faults, from incorrect collections to inefficient active search. Early identification of these children in which screening was unsatisfactory is essential, emphasizing the importance and efforts to not miss them. In the case of a failed test, healthcare professionals must be prepared to recognize the main symptoms and signs of the disease.